Peal factor of signals of 5G mobile service systems - V. M. Kozel; D. A. Podvornaya; K. A. Kovalev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This article discusses the possible formats of signals of 5G mobile communication networks (NR, IMT-2020): configurations of the number of resource blocks and frequency shifts of subcarriers. modulation schemes, organizations of the physical level, as well as the broadband signals of these networks and, as a result, the need for introducing a margin on the linearity of the transceiver’s paths to eliminate distortion or the manifestation of blocking effects when the signal interferes with third-party means. We analyze the characteristics of the dynamic range of the signals from IMT-2020 ground mobile systems and make a conclusion about the noise-like signals. To find the ratio of the maximum amplitude to its average value and a given ratio not exceeded with a given probability, the Matlab mathematical models were used. We infer that the law of probability distribution of the module of the instantaneous amplitude of the 5G signals corresponds to the distribution characteristic of narrow-band radio noise. Based on the study, the peak factor of the signal of the IMT-2020 ground mobile systems for various variations is obtained and a sufficient level of power reserve is provided to ensure, with high probability, the transmission of the 5G signals through radio paths, eliminating signal distortion. The results of this study were applied in the examination of the electromagnetic compatibility of radio electronic devices of cellular mobile communications with existing and promising electronic means of civil and special purposes and in the study of the protection of ground satellite stations from the effects of radio electronic means of IMT-2020 cellular mobile telecommunication networks located at border territories.